One-loop Holography with Strings in AdS₄ × CP³ - David, Marina (2019)
We compute the one-loop effective action of string configurations embedded in AdS₄ × CP³ which are dual to ⅙-BPS latitude Wilson Loops in the ABJM theory. To avoid ambiguities in the string path integral we subtract the ½-BPS case. The one-loop determinants are computed by Fourier-decomposing the two dimensional operators and then using the Gel'fand-Yaglom method. We comment on various aspects related to the regularization procedure, showing the cancellation of a hierarchy of divergences. After taking into account an IR anomaly from a change in topology, we find a precise agreement with the field theory result known from supersymmetric localization.